(untitled) - Elsayed Makki Elbishr Ali Hassan, Ibrahim Babikir Elhag, Li Ting Lin, Hassan Suleiman, Yousef A. Baker El-Ebiary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Reaching successful language education requires correct scientific steps based on clear methodological foundations that a person adopts to achieve his aspirations in this field. For this reason, there are differing views among researchers and scientists as they search for the most scientific necessities to reach an effective curriculum in second language education. The theories of modern researchers in this field varied, since the theories of e-learning emerged into the scientific arena, and the divergence between them increased even more since the emergence of applied linguistics, especially educational linguistics, as it is a branch of applied linguistics, and it intersects with the education sciences in the interest in educational problems that have a linguistic basis. It is a science that studies the teaching of languages and its techniques, and the forms of organizing the learning situations to which the learner is subject and taking into account their reflection on the individual and society in terms of developing mental abilities, enhancing conscience and directing social ties. With the theories of learning that differ among themselves in explaining the best way for how human learning takes place and the best ways in that. That is why this research focused on showing language levels, objectives of linguistic communication, stages of language acquisition and linking it to the communication process, as well as clarifying some e-learning strategies.